Knowledge and Practice of Emergency Physicians Regarding Food-borne Disease Surveillance at Hamad General Hospital in Qatar - Chehab, Mohamad A (Cureus, 2019)
Introduction According to the World Health Organization (WHO), foodborne diseases (FBD’s) have become a global health issue. In Qatar, foodborne diseases are among the top ten events reported to the Ministry of Public Health. Efforts to enhance FBD surveillance cannot succeed without involving the emergency department (ED), which is typically the first point of contact for the FBD victims with the healthcare system. Therefore, we aimed to explore the knowledge and practices of emergency physicians regarding stool sample collection as part of FBD surveillance efforts in Qatar. Methods A cross-sectional study was conducted at the ED of Hamad General Hospital (HGH) between July 22 and September 12 of 2018. The enrolled participants were invited to participate in an online survey at the “QSurvey” platform. The data was analyzed using Microsoft Excel (Version 2016). Descriptive statistics such as frequency tables, proportions, and percentages were applied as appropriate. Results A total of 65 responses (response rate: 29.27%) were received within the duration of the study. Most participants were specialists (45%), graduated between 2000 and 2013 (64%), and worked for one year or more at HGH-Hamad Medical Corporation (95%). Regarding their knowledge of FBD surveillance, most participants (80%) reported that a stool culture is a necessary laboratory investigation for patients with acute bloody diarrhea and fever. Also, a large percentage of physicians identified salmonella (75%), Clostridium difficile (70%), and E.coli O157:H7 (70%) as pathogens of nationally notifiable diseases. Regarding the respondents’ practice towards FBD surveillance, almost three-quarters of the physicians (72%) who encountered a patient with acute diarrhea did not order a stool culture. Subsequently, about two-thirds (62%) of the participants who requested a stool culture reported not following up on the results of such request. Regarding the history taken from patients with acute diarrhea, a large percentage of respondents reported asking about the patient’s travel history (100%), presence of any sick contacts (93.6%), and presence of any associated symptoms (abdominal pain, fever, bloody stool) as well as other details. Conclusion The current research identified several gaps regarding the knowledge and practice of emergency physicians towards the surveillance of foodborne disease. Such results serve as a basis for future research and intervention strategies to augment surveillance activities related to food-borne diseases in the State of Qatar.